ANALISIS RASIO KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PADA PT PERKEBUNAN NUSANTARA V PEKANBARU PERIODE 2014-2018 - Suci Rahmadani; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to measure and analyze financial performance at PT Perkebunan Nusantara V Pekanbaru period 2014-2018 using the ratio of liquidity, solvency, activity, and profitability based on the Decree of the Minister of State-Owned Enterprises Number: KEP-100/MBU/2002.The data used in this research are the financial statements of PT Perkebunan Nusantara V Pekanbaru, namely the balance sheet report for the period 2014-2018 and the profit and loss statement for the period 2014-2018. This research data is obtained through documentation and interviews. The data analysis technique used is to calculate the ratio of liquidity, solvency, activity, and profitability.The results showed that: (1) Liquidity level at PT Perkebunan Nusantara V Pekanbaru for the period 2014-2018 is in fairly good condition, (2) Solvency rate at PT Perkebunan Nusantara V Pekanbaru period 2014-2018 is in poor condition, (3) Activity Level at PT Perkebunan Nusantara V Pekanbaru period 2014-2018 is in excellent condition, (4) Profitability level at PT Perkebunan Nusantara V Pekanbaru period 2014-2018 in poor condition, (5) overall, the financial performance of PT Perkebunan Nusantara V Pekanbaru for the period 2014-2018 is in a fairly good condition and in the future needs to be improved again for more maximum performance. Keywords : Financial Performance, State-Owned Enterprises Number: KEP-100/MBU/2002.